Examining the Association Between Serum Leptin and Sarcopenic Obesity - Yang ZY (Dove Medical Press, 2021)
Zhe-Yu Yang,1,2 Wei-Liang Chen2– 4 1Department of General Medicine, Tri-Service General Hospital; and School of Medicine, National Defense Medical Center, Taipei, Taiwan, Republic of China; 2Division of Family Medicine, Department of Family and Community Medicine, Tri-Service General Hospital; and School of Medicine, National Defense Medical Center, Taipei, Taiwan, Republic of China; 3Division of Geriatric Medicine, Department of Family and Community Medicine, Tri-Service General Hospital; and School of Medicine, National Defense Medical Center, Taipei, Taiwan, Republic of China; 4Department of Biochemistry, National Defense Medical Center, Taiwan, Republic of ChinaCorrespondence: Wei-Liang ChenDivision of Geriatric Medicine, Department of Family Medicine, Tri-Service General Hospital, National Defense Medical Center, Number 325, Section 2, Chang-gong Road, Nei-Hu District, 114, Taipei, TaiwanTel +886-2-87923311 ext. 16567Fax +886-2-87927057Email weiliang0508@gmail.comObjective: Sarcopenic obesity is an emerging geriatric syndrome among elderly individuals. Studies revealed a complicated pathogenesis between sarcopenia and obesity. Leptin, a proinflammatory adipokine, has been implicated in the mechanism of sarcopenic obesity. This study investigated the relationship between serum leptin level and sarcopenic obesity.Methods: The study included 4063 participants aged 60 years and older from the NHANES III database. Sarcopenia was defined as a skeletal muscle index (SMI) less than one standard deviation below the young adult value. Obesity was defined as a body mass index (BMIF) over 30 kg/m2. Multivariate regression analysis was performed to examine the association between serum leptin level and sarcopenic obesity.Results: In adjusted models, serum leptin level was positively correlated with BMI (β: 1.33, p value < 0.001) and negatively correlated with SMI (β: − 0.091, p value = 0.001). A significant association between serum leptin level and sarcopenic obesity was found in multivariate analysis (β: 4.011, p value=0.014).Conclusion: Our study demonstrated that serum leptin level was related to an increased risk of sarcopenic obesity. This epidemiologic finding suggests that leptin may play a role in sarcopenic obesity.Keywords: serum leptin levels, sarcopenia, sarcopenic obesity